Heterogeneity in polyamine metabolism dictates prognosis and immune checkpoint blockade response in hepatocellular carcinoma - Jianyan Pan; Zhong Lin; Qinchun Pan; Tao Zhu (Frontiers in Immunology)
Immune checkpoint blockade holds promise in hepatocellular carcinoma (HCC) treatment, but its efficacy remains limited. Dysregulated polyamine metabolism and its interaction with oncogenic pathways promote tumor progression. However, the heterogeneity of polyamine metabolism and its effects on the immune microenvironment and response to immunotherapy in HCC remain unclear. Here, we aimed to investigate the prognostic and immunotherapeutic implications of polyamine metabolism in HCC. Based on polyamine-related genes, HCC patients were categorized into two clusters with distinct survival outcomes. We developed a polyamine-related signature, termed PAscore, which was found to be a strong predictor of both poor prognosis and reduced immunocyte infiltration. Notably, a high PAscore was also associated with decreased sensitivity to immunotherapy. Within the HCC microenvironment, malignant cells exhibited polyamine metabolic heterogeneity, those with high polyamine metabolic activity showed altered hallmark pathway signatures and increased communication with myeloid cells. In vitro experiments suggested that FIRRE, the gene with the greatest impact on the PAscore, significantly contributed to HCC proliferation and metastasis. This study underscores the potential of our polyamine-related signature in predicting the prognosis and immunotherapy response in HCC patients, and also reveals the polyamine metabolic heterogeneity among HCC cells that influences their crosstalk with infiltrating myeloid cells.